Invasion of Arion Vulgaris and its Projected Ecological Impact in Armenia (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Invasive alien species are one of the important factors of global biodiversity changes with the impact on ecosystems, economies and the quality of human lives. Spanish slug, Arion vulgaris is one of the dangerous invasive slugs of Europe and Asia, resulting biodiversity lost and agriculture damages. It has been recorded from the northern part of Armenia in 2022, which was the second record for the Caucasus, but first for the Transcaucasia. Our research goal was to study the population dynamics of the new invasive species to evaluate potential distribution and ecological impact. Field studies have been performed in the areas of species current distribution. It has been reported that species in the areas of its current distribution is damaging plants and crops in the gardens, and in the forested areas. Farmers mostly are using pesticides as a fighting tool against this pest. Based on the species habitat pReferences:and global climate change species will likely distribute all over Armenia within the next decade, impacting not only agriculture zones, but natural forested habitats as well.
Keywords: arionidae; invasive species; climate change; mollusca